2019
DOI: 10.1111/dpr.12456
|View full text |Cite
|
Sign up to set email alerts
|

The economics of China's engagement with Africa: What is the empirical evidence?

Abstract: Motivation In the last decade, economic and political ties between China and African countries grew fast, fuelling a heated debate about the implications for the latter and for the global system of China's engagement in Africa. Purpose The article reviews the existing evidence on the nature, causes and impact of China's economic engagement in Africa. Approach and methods The review focuses mainly on the economic literature with a quantitative focus. Findings China's reasons to engage with Africa are not so dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…On the part of China, about 40% of its total FDI (see Figure 2 for China's FDI stocks by sector) to Africa go into the resource‐endowed countries (Gold et al., 2019; Rasiah & Gachino, 2004; Rasiah et al., 2010; Shen & Fan, 2014). This pattern of Chinese engagement with resource‐rich African countries captured global imagination between 2006 and 2008 and was reported in UNCTAD and trade statistics databases, showcasing the resources exporting countries in Africa as a top beneficiary of FDI from a developing nation like China (Alabi et al., 2011; Gold, et al., 2019; Martuscelli, 2020; Taylor, 2015).…”
Section: Introductionmentioning
confidence: 62%
“…On the part of China, about 40% of its total FDI (see Figure 2 for China's FDI stocks by sector) to Africa go into the resource‐endowed countries (Gold et al., 2019; Rasiah & Gachino, 2004; Rasiah et al., 2010; Shen & Fan, 2014). This pattern of Chinese engagement with resource‐rich African countries captured global imagination between 2006 and 2008 and was reported in UNCTAD and trade statistics databases, showcasing the resources exporting countries in Africa as a top beneficiary of FDI from a developing nation like China (Alabi et al., 2011; Gold, et al., 2019; Martuscelli, 2020; Taylor, 2015).…”
Section: Introductionmentioning
confidence: 62%
“…In one account, this amounts to a 'transfer of excess domestic industrial capacity to low-wage, youth-rich developing countries; and portfolio diversification of international investment away from what are presently lowyield US bonds' (Johnstone 2019, p. 52). Hitherto, China's engagement has entrenched African countries' role as exporter of primary commodities, and importers of manufactures, helping to driving non-equitable growth without diversification and with limited employment generation in the process (Martuscelli 2019;Chakrabarty 2016;Hodzi 2018).…”
Section: )mentioning
confidence: 99%
“…The trade pattern between Africa and China has been motivated by the endowment-based Heckscher-Ohlin trade theory, as Africa exports its abundant natural resources to, and imports industrial and manufactured goods from China (Eisenman, 2012;Mlambo, Kushamba, & Simawu, 2016). While some studies have suggested that China-Africa trade may reinforce Africa's resources dependence and cause de-industrialization of the region (Ado & Su, 2016;Geda, Mosisa, & Assefa, 2013;Martuscelli, 2018) others pointed out that the trade pattern between China and Africa would be more beneficial to Africa's growth and development if handled with great care, as it tends to bridge the current infrastructure gap and generate funds (Eisenman, 2012;Nowak, 2016). Another cause is the economic diplomacy and development assistance offered by China to its trading partners.…”
Section: Introductionmentioning
confidence: 99%